An epigenetic view of B‐cell disorders. Issue 3 (20th January 2015) - Alberghini, Federica; Petrocelli, Valentina; Rahmat, Mahshid; Casola, Stefano
Abstract : B‐cell development is a multistep process sustained by a highly coordinated transcriptional network under the control of a limited set of transcription factors. Epigenetic mechanisms, including DNA methylation, histone posttranslational modifications and microRNAs act in concert with transcription factors to promote lineage commitment, define and sustain cell identity and establish heritable cell‐type‐ and stage‐specific gene expression profiles. Epigenetic modifiers have recently emerged as key regulators of B‐cell development and activation. Central to B‐cell‐mediated immunity are germinal centers, transient structures formed in secondary lymphoid organs where antigen‐specific B cells undergo intense proliferation, immunoglobulin somatic hypermutation and isotype switching, to generate ultimately long‐lived memory B cells and terminally differentiated plasma cells expressing high‐affinity antibodies. Deregulation of one or more epigenetic axes represents a common feature of several B‐cell disorders arising from germinal center B cells, including autoimmunity and lymphoma. Moreover, the hijacking of epigenetic determinants is central to the ability of the B‐lymphotropic Epstein–Barr virus (EBV) to establish, via the germinal center reaction, life‐long latency and occasionally contribute to malignant B‐cell transformation. In the light of recent findings, this review will discuss the relevance of epigenetic deregulation in the pathogenesis of B‐cell diseases. Understanding how specific epigenetic alterations contribute to the development of lymphomas, autoimmunity and EBV‐associated disorders is instrumental to develop novel therapeutic interventions for the cure of these often fatal pathologies. Abstract : The March 2015 issue contains a Special Feature on the epigenetic mechanisms underlying health and disease. Epigenetic modifications to chromatin influence the transcriptional status of our genes. Thus, understanding the epigenetic mechanisms that regulate immune cell fate are of great importance as they will provide insight into not only how to boost immune responses but also alter harmful ones such as autoimmunity and cancer. Immunology and Cell Biology thanks the coordinators of this Special Feature ‐ Rhys Allan ‐ for his planning and input.